1991
DOI: 10.1007/bf00282635
|View full text |Cite
|
Sign up to set email alerts
|

Structural genes of glutamate 1-semialdehyde aminotransferase for porphyrin synthesis in a cyanobacterium and Escherichia coli

Abstract: In bacteria 5-aminolevulinate, the universal precursor in the biosynthesis of the porphyrin nucleus of hemes, chlorophylls and bilins is synthesised by two different pathways: in non-sulphur purple bacteria (Rhodobacter) or Rhizobium 5-aminolevulinate synthase condenses glycine and succinyl-CoA into 5-aminolevulinate as is the case in mammalian cells and yeast. In cyanobacteria, green and purple sulphur bacteria, as in chloroplasts of higher plants and algae a three step pathway converts glutamate into 5-amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

1992
1992
1994
1994

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 63 publications
0
40
0
Order By: Relevance
“…In addition, a termination codon was identified upstream of the open reading frame and in the same reading frame, showing that the entire coding region was present in the cloned cDNA. The putative protein shared 79% identity with the GSA aminotransferase expressed in barley leaves (Grimm, 1990; with bacterial aminotransferases (Elliott et al, 1990;Grimm et al, 1991). This identity, along with the observed complementation of the GSA aminotransferase structural gene mutant of E. coli (Table 11), strongly suggests that the cloned cDNA encodes a soybean GSA aminotransferase.…”
Section: Soybean Nodule Cdnamentioning
confidence: 82%
“…In addition, a termination codon was identified upstream of the open reading frame and in the same reading frame, showing that the entire coding region was present in the cloned cDNA. The putative protein shared 79% identity with the GSA aminotransferase expressed in barley leaves (Grimm, 1990; with bacterial aminotransferases (Elliott et al, 1990;Grimm et al, 1991). This identity, along with the observed complementation of the GSA aminotransferase structural gene mutant of E. coli (Table 11), strongly suggests that the cloned cDNA encodes a soybean GSA aminotransferase.…”
Section: Soybean Nodule Cdnamentioning
confidence: 82%
“…This apparent discrepancy was explained, when it was discovered that E. coli synthesizes 5-aminolevulinic acid from glutamate by the threestep C5 pathway (Avissar and Beale, 1989). The hemL gene was shown to encode GSA-aminotransferase (Grimm et al, 1991), while the function of the hem4 gene remained unclear. The E. coli hemA gene was cloned and sequenced simultaneously by three groups (Drolet et al, 1989;Li et al, 1989;Verkamp and Chelm, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Asterisks indicate the positions of amino acids found in the consensus fingerprint sequence of ADP binding proteins (Wierenga et al, 1986 The predicted amino acid sequence of the Arabidopsis GSAl protein (Atgsa) was aligned with the predicted amino acid sequences of the GSA-AM proteins from soybean (Soygsa; Sangwan and OBrian, 1993), barley (Blygsa; Grimm, 1990), E. coli (Ecogsa;Grimm et al, 1991), S. typhimurium (Stygsa; Elliott et al,199D), Synechococcus (Syogsa; Grimm et al, 1991), and 8. subtilis (Bacgsa; Hansson et al, 1991) using the Pileup program in the sequence analysis software of the Wisconsin Genetics Computer Group (Devereux et al, 1984). A dash represents an amino acid identical to that in the Arabidopsis enzyme at that particular position, whereas an asterisk indicates a position with identical amino acid residues in all seven sequences, and a dot within a sequence represents a gap that was introduced to maximize homology.…”
Section: K T V I ------A C-lv---l---a -D I T I V ---Qr-sqdlan S -A -mentioning
confidence: 99%
“…Like other aminotransferases, GSA-AM utilizes pyridoxal phosphate as a cofactor. Sequence information is available for GSA-AM genes from E. coli (Grimm et al, 1991), 6. subrilis (Hansson et al, 1991), S. typhimurium (Elliott et al, 1990), Synechococcus (Grimm et al, 1991), barley (Grimm, 1990), and soybean (Sangwan and OBrian, 1993). Comparison of the deduced amino acid sequences revealed that GSA-AM proteins are very similar to one another; e.g., the Synechococcus and barley enzymes are 70% identical.…”
Section: Introductionmentioning
confidence: 99%